PENGEMBANGAN MODUL SUSTAINABLE PROJECT-BASED LEARNING (S-PjBL) BERBANTUAN AUGMENTED REALITY SEBAGAI INOVASI PEMBELAJARAN GREEN CHEMISTRY BAGI CALON GURU KIMIA - Prasetya, Cyndi; Maisarah; Qumarani, Yara; Fahira, Nazihan; Wahyuni, Naila (Lantanida Journal, 2025)
While its application in higher education is frequently limited by the lack of contextual and interactive teaching materials and engaging visualization of abstract concepts, green chemistry education is crucial for developing environmental awareness and sustainable attitudes among pre-service chemistry teachers. The objective of this work was to create a green chemistry learning module using augmented reality (AR) and Sustainable Project-Based Learning (S-PjBL). Purposive sampling was used to choose 28 pre-service chemistry teachers for the study, which used the ADDIE development model. Expert validation and user response questionnaires were used to collect data, and percentage average scores were used for quantitative analysis. The module received a 92.22% validation score from material experts and a 90.56% (very feasible) validation score from educational technology experts, according to the results. Lecturers scored 94.44% on practicality assessments, while students scored 90.12% (very practical). Students' comprehension of green chemistry, sustainable project implementation, and connections to actual environmental challenges were all bolstered by the program. To sum up, the AR-assisted S-PjBL green chemistry program is very realistic and useful for educating aspiring chemistry teachers. According to the results, combining S-PjBL with AR improves student engagement, fortifies 21st-century abilities, increases knowledge of green chemistry, and promotes high-quality education.